The Role of Podcasts as an Alternative Media for Learning and Distribution of Audio Based Content - I Tarmawan; R Rusdiyana; A D. P. Salim; A P Ulpah (International Journal of Research and Applied Technology (INJURATECH), 2021)
In the era of communication technology development, podcasts have become a means for audio-based content distribution. The purpose of this research is to explain the effectiveness of podcasts as alternative media fornlearning and audio-based content distribution. The method used in this research was a descriptive method with interview and observation techniques to obtain information. The results showed that with the increasing development of podcast media, many people use it as a learning medium. The conclusion obtained from this research is that with the existence of podcast media, learning can be done variedly and innovatively. Podcasts are also rated as an effective medium without the need to take so much effort to be able to get creative and innovative content in them. Creators can also share materials that they master easily, time-savingly, and more affordable to audiences.